Evaluation of Senior Dental Students’ General Attitude towards the Use of Rubber Dam: A Survey among Two Dental Schools - Jale Tanalp; Müzeyyen Kayataş; Elif Delve Başer Can; Mehmet Baybora Kayahan; Tuğçe Timur (The Scientific World Journal)
The purpose of this study was to evaluate the general attitude of senior dental students towards rubber dam use, specifically focusing on endodontic practices prior to starting to serve community. Questionnaires were distributed to senior year students of a private school and a state school in Istanbul. Questions were asked about areas where the students used rubber dam, its advantages and difficulties, and whether they agreed or disagreed with some aspects of the rubber dam. The private school students rated isolation whereas those of the state school selected prevention of aspiration which the top advantage rubber dam provides. Students of the state school agreed with the opinion that isolation cannot be achieved without rubber dam and it extended the procedure with a significantly higher ratio compared to the private school. Within the limitations of the present study, it can be concluded that the perceptions of dental students on rubber dam needs to be improved and strategies should be developed so that this valuable adjunct will comprise one of the indispensable elements of dental care.